Answer:
The two lines in the graph are parallel, so it is B. Inconsistent since there is no solution.
Answer:
the answer would be B inconsistent
Answer: a survey
Step-by-step explanation:
Answer:
y = -x + 4
Step-by-step explanation:
x + y = 6 => y = -x + 6
The line that parallel to y = -x + 6 has same slope so m = -1
Using coordinates (-4,8)
y = mx + b
8 = (-1)(-4) + b
8 = 4 + b
b = 4
then y = -x + 4
Answer: 3.675 seconds
Step-by-step explanation:
Hi, when the object hits the ground, h=0:
h=−16t^2+48.6t+37.5
0=−16t^2+48.6t+37.5
We have to apply the quadratic formula:
For: ax2+ bx + c
x =[ -b ± √b²-4ac] /2a
Replacing with the values given:
a=-16 ; b=48.6; c=37.5
x =[ -(48.6) ± √(-48.6)²-4(-16)37.5] /2(-16)
x = [ -48.6 ± √ 4,761.96] /-32
x = [ -48.6 ± 69] /-32
Positive:
x = [ -48.6 + 69] /-32 = -0.6375
Negative:
x = [ -48.6 - 69] /-32 = 3.675 seconds (seconds can't be negative)
Feel free to ask for more if needed or if you did not understand something.
The object to hit the ground takes 3.675 seconds.
An initial velocity of 48.6 feet per second
When the object hits the ground, h=0:
h=−16t²+48.6t+37.5
0=−16t²+48.6t+37.5
We have to apply the quadratic formula:
For: ax²+ bx + c
x =[ -b ± √b²-4ac] /2a
Substituting with the values given:
a=-16 ; b=48.6; c=37.5
x =[ -(48.6) ± √(-48.6)²-4(-16)37.5] /2(-16)
x = [ -48.6 ± √ 4,761.96] /-32
x = [ -48.6 ± 69] /-32
Positive:
x = [ -48.6 + 69] /-32 = -0.6375
Negative:
x = [ -48.6 - 69] /-32 = 3.675 seconds (seconds can't be negative)
For such more questions on object
#SPJ6
Answer:
a) She only used the additive inverse of 10m when combining like terms.
Step-by-step explanation:
Given : Holly finds that
First we open the bracket by multiplying minus sign in it, we get
Combining like terms we get, we get
→ correct answer.
When we compare the correct answer to the answer given by Holly, the first term is same in both the answers,
Therefore, She only used the additive inverse of 10m when combining like terms.
Answer:
answer A
Step-by-step explanation:
{½, 2}
{½, –2} Use the quadratic formula to solve 2y2 – 5y = –2.
Answer:
1/2, 2
Step-by-step explanation:
i took the test